Business Model Canvas dan Social Media Marketing untuk Meningkatkan Kapasitas Pengusaha Mikro di Kabupaten Pangkep - Anugrayani Bustamin (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Community service has been done to improve the performance and capacity of the Pelita Desa Farmers Group in Pangkep Regency. Pelita Desa Farmers Group is a group of "Pamelo" orange entrepreneurs in Attangsalo Village, Ma’rang District, Pangkep Regency. The socialization activity was attended by 15 participants who were members of the Pelita Desa Farmer Group and several community leaders also participated. The results of the analysis of the situation and conditions found several problems that are being faced by Pelita Desa Farmers Group, namely the ongoing business has not gone through the process of business analysis, social media marketing and branding are still not used. So that in this service activity the introduction of Business Model Canvas (BMC) was carried out by conducting business translation in a simple but effective way to look holistically at a startup or business. Furthermore, the introduction of social media marketing is also carried out to support business groups, improve performance to be sustainable and develop better. This is considered necessary to be a turning point for business groups in increasing efforts to progress and face the era of globalization.